1998
DOI: 10.1212/wnl.50.3.708
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuritis

Abstract: We investigated the paraclinical profile of monosymptomatic optic neuritis (ON) and its prognosis for multiple sclerosis (MS). The correct identification of patients with very early MS carrying a high risk for conversion to clinically definite MS is important when new treatments are emerging that hopefully will prevent or at least delay future MS. We conducted a prospective single observer and population-based study of 147 consecutive patients (118 women, 80%) with acute monosymptomatic ON referred from a catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
119
1
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(133 citation statements)
references
References 14 publications
8
119
1
5
Order By: Relevance
“…Accordingly, relapse frequency has previously been recognised to be higher in younger patients [8,13]. Also, the observation that patients who had positive CSF findings convert more frequently has been reported previously [18,19]. The finding that patients in whom the presenting episode was treated with intravenous steroids had a higher conversion rate appears to be somewhat surprising in the light of previous observations, mainly from the Optic Neuritis Treatment Trial, which indicated that steroids might have some protective effects [4].…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, relapse frequency has previously been recognised to be higher in younger patients [8,13]. Also, the observation that patients who had positive CSF findings convert more frequently has been reported previously [18,19]. The finding that patients in whom the presenting episode was treated with intravenous steroids had a higher conversion rate appears to be somewhat surprising in the light of previous observations, mainly from the Optic Neuritis Treatment Trial, which indicated that steroids might have some protective effects [4].…”
Section: Discussionmentioning
confidence: 94%
“…Determining which patients have a higher risk of conversion to MS is important, as studies suggest that there may be a benefit from early immunomodulatory treatment in patients with clinically isolated syndrome (CIS), including ON [4][5][6][7][8][9][10]. Although the presence of one or more lesions on baseline brain MRI has been identified as the strongest predictor of MS conversion [3,[11][12][13][14][15][16], there are patients with normal baseline MRI who also develop MS and predictors of conversion are still to be determined in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Optic neuritis is a very common early symptom in MS patients, with approximately 30-60% of patients experiencing visual problems associated with inflammation and demyelination in the optic nerve [6,7]. Optic nerve lesions have also been reported in EAE [8][9][10], and may represent an early event in the progression of anti-myelin immune responses [11].…”
Section: Introductionmentioning
confidence: 99%